(untitled) (Research, Society and Development, 2022)
The present experience report presents an activity developed in the Physical Education classes of a municipal school in Fortaleza, between the months of April and May 2022. The proposed activity refers to the experience and enjoyment of a genuinely Brazilian and poorly explored sport, the Zaccarobol or Zbol. For this, the emergence and evolution of Zbol was discussed, its rules and foundations, a theoretical discussion that contributed to the continuation of the following meetings. In this way, the objective is: to report the experience of schoolchildren with the implementation and effectiveness of a genuinely Brazilian alternative sports modality, Zaccarobol, in Physical Education classes. In the methodological procedure, exploratory research of the bibliographic type was used in order to support the theoretical discussion. After the development of the modality, a questionnaire was applied to the students. From the positions of these through the questionnaire, it was noticed that the effectiveness of this modality provided the students with the stimulus to accept new possibilities of practicing sports, in addition to the possibility of expressing creativity in the production of implements, as well as improving their knowledge. in relation to the exposed theme.